Critical analysis of long-term vision of Lithuanian Science and Studies: seeking for most realistic scenario of higher education development - Putrienė, Nijolė; Vaičekauskienė, Snieguolė (Pedagogika, 2014)
On the basis of the scientific literature and document analysis long-term vision of Lithuanian Science and Studies “Learning Lithuania 2030” is analyzed in this article. This fist part deals with the situation of education in Europe, with particular emphasis on higher education and the search for factors affcting the Lithuanian higher education situation. Unique situation of Lithuanian higher education allows assume that in the future Lithuanian Higher Education will develop on its own way. The second part of the article discusses long-term vision of Lithuanian Science and Studies “Learning Lithuania 2030” and highlights factors affcting development of higher education. The third paragraph is devoted to discuss the manner in which these factors inflence the Lithuanian science and studies nowadays. The fourth paragraph discusses possibilities to achieve learning society in Lithuania until 2030 and highlights the assumptions that are necessary in order to achieve that quality of society. Conclusions of the article emphasize that active university initiative to educate the society could move forward changes that will drive the development of Lithuania towards a learning society, where scientific knowledge is the axes of life, economic activity, consumption, employment and development.